Mentoring dan Coaching sebagai Strategi Pengembangan Pendidikan Kewirausahaan: Studi Fenomenologi - Wijaya, Oscarius Yudhi Ari; Radianto, Wirawan ED (Jurnal Aplikasi Manajemen, 2016)
Entrepreneurship has been gained attention at the institutions of higher education in Indonesia. The entrepreneurship courses is a necessity for college student. The qualitative research with phenomenology was trying to explore the effectiveness of Mentoring and Coaching Strategy in the process of looking for ideas and transferring knowledge to the learners (students) during the Entrepreneurship education. Mentoring and Coaching have differences and similarities, briefly mentoring has a meaning giving direction and coaching meanslooking for ideas / opinions of students in solving problems that occur in the project based learning experienced by students.The problem occurs in the educator (facilitator) is to answer the question whether it should be mentoring or coaching.The findings in this study indicate that the facilitators have more difficulty in doing coaching than mentoring and in the process of coaching is not allowed to give advice to the studentbecause all the settlement ideas must come from their own and there are still many facilitators were doing more mentoring than coaching.